Household Finance and Consumption Survey: A comparison of the main results for Malta with the euro area - Valentina Antonaroli; Warren Deguara; Aleandra Muscat (Central Bank of Malta, 2023)
This paper compares the main findings from the fourth wave of the Household Finance and Consumption Survey (HFCS) for Malta with those for the euro area. This comparative report finds that in 2020 the median Maltese household held more real and financial assets than households in the euro area. The median value of total liabilities of indebted Maltese households also stood higher than in the euro area. Despite higher total liabilities, the debt-toasset ratio indicates that Maltese households have a significantly higher amount of assets to back their debt. Largely reflecting the higher prevalence of homeownership in Malta, the median net wealth in Malta was estimated to be significantly higher than in the euro area. At the same time, gross income of Maltese households stood notably lower when compared to the euro area. Results also show that Maltese households spend more on food but considerably less on utilities compared to euro area counterparts. Against different macroeconomic and socio-demographic backgrounds, the survey results highlight heterogeneous developments between Malta and the euro area as a whole. Furthermore, euro area averages mask notable cross-country differences.
Keywords: D1; D2; E21; O57; 330; Household finance; consumption; wealth; survey data; comparative studies